Solution chemistry-based nano-structuring of copper dendrites for efficient use in catalysis and superhydrophobic surfaces - Bakthavatsalam, Rangarajan; Ghosh, Subrata; Biswas, Ratul Kumar; Saxena, Aayushi; Raja, Alagar; Thotiyl, Musthafa Ottakam; Wadhai, Sandip; Banpurkar, Arun G.; Kundu, Janardan (RSC Advances, 2016)
Despite their performance and economic advantages over Ag and Au, there have been no focused research efforts on the nano-structuring of Cu dendrites with respect to fine-tuning their structure/morphology towards the efficiency enhancement of suitable applications. Reported here is a simple, versatile, environmentally-friendly and galvanic replacement reaction-based solution chemistry methodology to synthesize highly nano-structured copper dendrites targeted towards the efficiency enhancement of desired applications. Herein, copper is deposited galvanically on an Al foil in the presence of NaCl/HCl, wherein the chloride anions augment an uninterrupted replacement reaction. The growth process of Cu dendrites has been probed in detail. The presence of acid, the type of Cu2+ precursor salt, the Cu2+ ion concentration, the surfactant concentration and the reaction temperature are all demonstrated to provide useful means of modulating the surface structure/morphology of the dendrites. Notably, dendrites formed in the presence of acid are found to be highly nano-structured. Moreover, it is also found that the morphology/structure of the obtained Cu deposit depends considerably upon the choice of the Cu2+ precursor salt, a parameter that has been completely overlooked in the past. The acid-induced nano-structuring of the dendrites is exploited for enhancing their efficiency in the catalytic reduction of para-nitrophenol and for fabricating self-cleaning superhydrophobic surfaces. These nano-structured dendrites are demonstrated to have the highest ever normalized rate constant for the catalytic reduction reaction. Superhydrophobic surfaces fabricated using these dendrites demonstrate excellent self-cleaning abilities, showing a high contact angle (159 degrees) with low contact angle hysteresis (2 degrees). This facile synthetic strategy for the fabrication of highly nano-structured Cu dendrites is expected to open up avenues for the production of Cu-based low-cost functional nano/micro-materials.